(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
The main objective of this study is to enhance the proficiency of conversational interaction in English between teachers and students at high schools situated in the Dong Nai province. The research framework is grounded on Vygotsky’s sociocultural theory, supplemented by Long’s theory of interaction, and Brown’s approach to teaching communicative English. Through a survey of 148 English teachers in Dong Nai high schools and subsequent data analysis employing SPSS 20 software, the research findings indicate that all four factors, namely belonging, expectation, relationship, and motivation, exert a positive and statistically significant influence on conversational interaction in English between teachers and students in this educational context. Based on the study’s outcomes, the author proposes several viable strategies to enhance teachers’ capacity for conversational interaction in English with their students. Such interventions are envisioned to be instrumental in elevating the overall educational quality, aligning it with international standards, and fostering heightened competitiveness with developed nations within the region. This endeavor represents a concerted effort to contribute to the ongoing advancement of language education in Vietnam.